2020
DOI: 10.3390/microorganisms8091298
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Maturation of the Phagosome: A Key Mechanism in Innate Immunity against Intracellular Bacterial Infection

Abstract: Phagocytosis is an essential mechanism in innate immune defense, and in maintaining homeostasis to eliminate apoptotic cells or microbes, such as Mycobacterium tuberculosis, Salmonella enterica, Streptococcus pyogenes and Legionella pneumophila. After internalizing microbial pathogens via phagocytosis, phagosomes undergo a series of ‘maturation’ steps, to form an increasingly acidified compartment and subsequently fuse with the lysosome to develop into phagolysosomes and effectively eliminate the invading path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 152 publications
(157 reference statements)
4
54
0
Order By: Relevance
“…Following the ingestion of bacteria, acidification by phagosomes and the fusion of phagosomes and lysosomes are two main characteristics of phagocyte maturation [58]. Our results showed a significant increase in phagosomal acidification of the GNP-and GOF-pretreated BMDMs following the ingestion of S. aureus and E. coli, as compared with the control BMDMs (Figure 4).…”
Section: The Gnps and Gofs In Phagosome Maturationmentioning
confidence: 61%
“…Following the ingestion of bacteria, acidification by phagosomes and the fusion of phagosomes and lysosomes are two main characteristics of phagocyte maturation [58]. Our results showed a significant increase in phagosomal acidification of the GNP-and GOF-pretreated BMDMs following the ingestion of S. aureus and E. coli, as compared with the control BMDMs (Figure 4).…”
Section: The Gnps and Gofs In Phagosome Maturationmentioning
confidence: 61%
“…Kureishi et al (1997) research has demonstrated that Rho‐kinase directly modulates smooth muscle contraction through myosin light chain phosphorylation, independently of the Ca 2+ ‐calmodulin‐dependent myosin light chain kinase pathway. In multicellular organisms, phagocytosis plays a role in maintaining cellular homeostasis by removing dead cells, microbes and cellular or foreign debris (Lee et al, 2020; Lee et al, 2020). Bandola‐Simon and Roche's (2019) research has shown that MLC2 in hepatopancreas tissue may resist the infection of Vibrio anguillae by triggering actin rearrangement and forming phagosomes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that IgG and IgM assessment is not very useful in identifying the stage and severity of the infection, but it can be used to diagnose polymerase chain reaction‐negative patients and perhaps get a grasp of the clinical course and disease severity. 39 , 41 , 42 , 43 …”
Section: Antibody Responses To Sars‐cov‐2mentioning
confidence: 99%